Does the global financial crisis and retrenchments affect the manufacturing industries labour productivity in Malaysia? / Nurhani Abd Ibrahim, Rosita Suhaimi and Chong Fen Nee - Abd Ibrahim, Nurhani; Suhaimi, Rosita; Fen Nee, Chong (Faculty of Administrative Science and Policy Studies, 2012)
This paper examines retrenchment activities since the global financial crisis occur and the effect of retrenchment and global financial crisis on the labour productivity of the manufacturing industries in Malaysia. Due to the crisis, many industries retrenched their workers to adjust to the declining demand in their respective industries. Two distinctive subindustries that have the highest retrenchment rates are the manufacture of radio, television and communication (27%) and manufacture of rubber and plastics (13.3%) out of total retrenchments within the last three years (2009-2011). The main reason for the retrenchments is the deteriorating demand for their products. Using panel data analysis with fixed effects on monthly data from 2003 till August 2011, the study finds that the 2008-2009 crisis has positively affected the labour productivity of the industries. The study also finds that the industries activities of recruiting and retrenching do not significantly affect their labour productivity regardless of their size. These findings suggest that the industries adjust their employment level not to improve their labour productivity but rather to respond to the changing demand of their products. With the country set to become a high-income economy by 2020, the industries have to change their employment and production strategy to ensure that they can improve their labour productivity and hence, increase their profitability.